Wildwood - Meloy, Colin; Ellis, Carson, 1975- (New York : Balzer + Bray, 2011)
Prue's life shifts from ordinary to extraordinary when her baby brother is kidnapped by a murder of crows and she must embark into the Impassable Wilderness, a dense forest in the center of Portland, Oregon, with her friend Curtis in tow, where the pair will encounter warring creatures, peaceful mystics, and other dark-minded, powerful figures.
Map on endpapers.
Booklist starred
School Library Journal starred
Voice of Youth Advocates (V.O.Y.A.)
Booklist starred, July 2011
Kirkus Review, July 2011
Keywords: Animals -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Missing children -- Juvenile fiction; Animals -- Fiction; Brothers and sisters -- Fiction; Fantasy; Missing children -- Fiction; Animals -- Fiction; Missing children -- Fiction; Siblings -- Fiction; Portland (Or.) -- Juvenile fiction; Portland (Or.) -- Fiction; Portland (Or.) -- Fiction; Fantastic fiction; Fantastic fiction